Label-free CARS microscopy through a multimode fiber endoscope - Tragardh, Johanna; Pikalek, Tomas; Sery, Mojmir; Meyer, Tobias; Popp, Juergen; Cizmar, Tomas (Optics Express, 2019)
Multimode fibres have recently been employed as high-resolution ultra-thin endoscopes, capable of imaging biological structures deep inside tissue in vivo. Here, we extend this technique to label-free non-linear microscopy with chemical contrast using coherent anti-Stokes Raman scattering (CARS) through a multimode fibre endoscope, which opens up new avenues for instant and in-situ diagnosis of potentially malignant tissue. We use a commercial 125 µm diameter, 0.29 NA GRIN fibre, and wavefront shaping on an SLM is used to create foci that are scanned behind the fibre facet across the sample. The chemical selectivity is demonstrated by imaging 2 µm polystyrene and 2.5 µm PMMA beads with per pixel integration time as low as 1 ms for epi-detection.
CRIS-Team Scopus Importer:2023-04-20